Polycyclic aromatic hydrocarbons at fire stations: firefighters’exposure monitoring and biomonitoring, and assessment of the contribution to total internal dose - Oliveira, Marta (2016)
This work characterizes levels of eighteen polycyclic aromatic hydrocarbons (PAHs) in the breathing airzone of firefighters during their regular work shift at eight Portuguese fire stations, and the firefighters’total internal dose by six urinary monohydroxyl metabolites (OH-PAHs). Total PAHs ( PAHs) concentra-tions varied widely (46.4–428 ng/m3), mainly due to site specificity (urban/rural) and characteristics (ageand layout) of buildings. Airborne PAHs with 2–3 rings were the most abundant (63.9–95.7% PAHs).Similarly, urinary 1-hydroxynaphthalene and 1-hydroxyacenaphthene were the predominant metabo-lites (66–96% OH-PAHs). Naphthalene contributed the most to carcinogenic PAHs (39.4–78.1%) inmajority of firehouses; benzo[a]pyrene, the marker of carcinogenic PAHs, accounted with 1.5–10%. Statis-tically positive significant correlations (r ≥ 0.733, p ≤ 0.025) were observed between PAHs and urinary OH-PAHs for firefighters of four fire stations suggesting that, at these sites, indoor air was their majorexposure source of PAHs. Firefighter’s personal exposure to PAHs at Portuguese fire stations were wellbelow the existent occupational exposure limits. Also, the quantified concentrations of post-shift uri-nary 1-hydroxypyrene in all firefighters were clearly lower than the benchmark level (0.5 mol/mol)recommended by the American Conference of Governmental Industrial Hygienists.